1996
DOI: 10.1046/j.1464-410x.1996.09287.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic instability of 3p12‐p21‐specific microsatellite sequences in renal cell carcinoma

Abstract: These results suggest that human chromosome region 3p14.3 distal to the hereditary t(3;8) translocation breakpoint and the region deleted in the U2020 lung cancer cell line might be involved in the tumorigenesis or progression of clear cell RCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 3 publications
(4 reference statements)
0
20
0
Order By: Relevance
“…Structural alterations for the first chromosomal region have been reported in the literature [25, 26, 27] in RCC. This is the first report to our knowledge on the incidence of 17q21 locus deletions in RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Structural alterations for the first chromosomal region have been reported in the literature [25, 26, 27] in RCC. This is the first report to our knowledge on the incidence of 17q21 locus deletions in RCC.…”
Section: Discussionmentioning
confidence: 99%
“…The familial form, associated with predisposition to an early-onset of multicentric RCC, was also characterised by balanced translocations t(3;8)(p21;q24) [33][34]. Loss of heterozygosity for the wnt-5a gene mapped to chromosome 3p14-21, was reported to affect the suppression of growth and repression of telomerase activity, and was described in nonpapillary RCC [35].…”
Section: Genomic Aspects Of Renal Cell Carcinomamentioning
confidence: 99%
“…MSI analysis has previously been used: i) to determine the genetic alterations involved in different renal tumor histotypes (19,28), ii) to study the possible inactivation of one or more tumor suppressor genes in renal cancer samples (25), and iii) to investigate the clonal origin of multifocal renal cell carcinomas (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated alterations in MMR genes [such as the human mutL homolog 1 (hMLH1) and the human mutS homolog 2 (hMSH2)] and the presence of MSI in human cancers, as well as in renal tumors (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). However, data on the incidence of MSI in renal cortical cancers is conflicting and the role of the MMR genes in these malignancies is still largely unknown.…”
Section: Introductionmentioning
confidence: 99%